Gestão organizacional da geração distribuída em concessionárias de energia elétrica no Brasil - Rosa, Carmen Brum (2019)
The transformation of the electricity sector towards a more diversified and sustainable electricity production has spread the importance of generation distributed from renewable sources. Despite the national scenario of distributed generation having an exponential growth, in September 2019 Brazil accumulated 135 MW of installed power, distributed in more than 110 thousand consumption units. From this perspective, projections for 2026 expect that photovoltaic energy will reach 3.3 GWp of installed capacity at 770,000 units, which would be enough to supply 0.6% of total national electricity demand. In Brazil, the electric power generation systems connected to the electric network near the load center grow through the compensation of credits, a model that was only possible after ANEEL (National Electrical Energy Agency) 482/2012 Normative Resolution. Although the systemic benefits associated with the expansion of distributed electricity generation are evident, regarding the distribution utilities, it is important to assess the challenges arising from the increased diffusion rate of these facilities. Given this scenario, for the utilities to achieve adequate performance and defend strategic positions in the electricity market, it is necessary to know and understand the dynamics of the main players in the business, structural and systemic areas, permeated by indicators capable of measuring and evaluating, in fact, their specific reality. Therefore, the use of a performance measurement system built on mathematical modeling capable of measuring the utility's organizational performance level was developed based on the Balanced Scorecard precepts. Thirty-two criteria-objectives were selected through the integrative review methodology, associated with the Delphi method, and allocated to the BSC strategic map, divided into four traditional perspectives: Financial, Customer, Internal Process and Learning and Growth. The mathematical modeling proposed the use of the AHP method to differentiate the degree of importance of the criteria-objectives under judgment of four groups of experts in the area: representatives of ANEEL and AGERGS, researchers with a scientific focus on DG, managers of distribution utilities and clients and associations in the area. The conception of the formulation for performance measurement relates a performance indicator to the achievement of the goal established for each criterion-objective, in order to verify the company's performance in that aspect. The model developed was applied in four distribution utilities in Brazil. None of them achieved the regular performance level, nor did they have a satisfactory position in the management of DG. This is due to the fact that the distribution utilities perceive DG as a threat to their current business models, and do not see it as a potential and profitable market. When relating these results to the indicator data established by ANEEL, it was noticed that the regulator does not have structured performance indicators to identify the current scenario of DG in the distribution utilities. In order to contribute to the sector, 19 strategic performance indicators were suggested for future discussions on compensation in proportion to the results stated in the indicators under review. In addition, a computational tool, with offline availability, was built to guide DG's management decision making at the distribution utilities. With this study, it becomes clear that the improvement of DG's management processes would allow distribution utilities to have an excellent position before the regulatory body. Beneficial adaptation to new realities is accessible through the use of a strategic tool for developing new organizational forms for the creation, delivery and value capture of DG.